# Thread: Help in rearanging an equation.

1. ## Help in rearanging an equation.

I couldn't figure out how to rearrange so i looked at the answer but it still didnt help.

If V = 12R / (r + R) , then R =

Vr / (12 - V)

We have to rearrange the equation to make R the subject.
Start by cross multiplying by (r + R); V (r + R) = 12R
Multiply out the bracket Vr + VR = 12R

I pulled this off a website, I can't figure out how they get to Vr + VR=12R
but I cant figure out how to get from that to Vr/(12-V)

2. Originally Posted by immunofort
I couldn't figure out how to rearrange so i looked at the answer but it still didnt help.

If V = 12R / (r + R) , then R =

Vr / (12 - V)

We have to rearrange the equation to make R the subject.
Start by cross multiplying by (r + R); V (r + R) = 12R
Multiply out the bracket Vr + VR = 12R

I pulled this off a website, I can't figure out how they get to Vr + VR=12R
but I cant figure out how to get from that to Vr/(12-V)
The can't. Do you mean can??

Vr + VR = 12R

=> V r = 12R - V R

Factorise the right hand side (R is a common factor):

=> V r = R (12 - V)

Divide both sides by (12 - V) to isolate R:

V r/(12 - V) = R. Viola!

3. Yeah i did mean can and thanks for that. It seems so simple once i realized that i had to factorise.